2002
DOI: 10.1291/hypres.25.99
|View full text |Cite
|
Sign up to set email alerts
|

Green Coffee Bean Extract and Its Metabolites Have a Hypotensive Effect in Spontaneously Hypertensive Rats

Abstract: The effects of a water-soluble green coffee bean extract (GCE) on blood pressure were investigated using spontaneously hypertensive rats (SHR). There was a dose-dependent reduction in blood pressure after a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(123 citation statements)
references
References 54 publications
2
119
0
2
Order By: Relevance
“…18 In spontaneously hypertensive rats (SHR), a single oral administration of 180, 360 and 720 mg kg -1 GCE (CGA content: 28%), respectively, reduced blood pressure (measured by tail cuff for 25 h) in a dose-dependent fashion: Systolic blood pressures(SBP) were reduced by 10-15 mm Hg from baseline 10 h after the ingestion of GCE at 720 mg kg -1 , and the effect persisted through the end of the experiment. However, GCE had no discernable effect in normotensive counterparts (control rats WKY).…”
Section: Effect Of Green Coffee Extracts On Blood Pressure In Animalsmentioning
confidence: 99%
“…18 In spontaneously hypertensive rats (SHR), a single oral administration of 180, 360 and 720 mg kg -1 GCE (CGA content: 28%), respectively, reduced blood pressure (measured by tail cuff for 25 h) in a dose-dependent fashion: Systolic blood pressures(SBP) were reduced by 10-15 mm Hg from baseline 10 h after the ingestion of GCE at 720 mg kg -1 , and the effect persisted through the end of the experiment. However, GCE had no discernable effect in normotensive counterparts (control rats WKY).…”
Section: Effect Of Green Coffee Extracts On Blood Pressure In Animalsmentioning
confidence: 99%
“…Recent animal and human studies reported an antihypertensive effect of chlorogenic acids in green coffee bean extract. 12,13 The relationship between the ingestion and the antihypertensive effect of brewed coffee from roasted coffee beans and blood pressure, however, is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further study is needed to clarify the changes in free and bound phenolics during processing. Ferulic acid exhibits an antioxidative activity (Sahidi et al, 1992;Ohta et al, 1994;Castelluccio et al, 1995;Ohta et al, 1997;Andreasen et al, 2001;Liyana-Pathirana and Shahidi, 2006) and has recently been reported to show depressor, anti-tumor, and anti-Alzheimer's activities (Mori et al, 1999;Yan et al, 2001;Suzuki et al, 2002;Mamiya et al, 2004). Therefore, rolled oats may also exhibit these effects.…”
Section: Resultsmentioning
confidence: 99%